CSR strategy composition and leaf traits for herbaceous plants in garden design - Fei Wang; Qiongwen Zhang; Peilu Huang; Cangshuan Li; Yan Li (Ecological Indicators, 2024)
Low community stability and sustainability, accompanied by high maintenance cost was an important ecological problem in planted herbaceous communities in many cities. Investigation showed that the overwhelmingly majority of garden designers ignored the subtle interactions between plants and plants in community itself, as well as the fitness of plants to certain environment. Fortunately, CSR strategy methodology based on leaf traits could be a useful tool for reflecting plant functional groups, thus we can have a deeper understanding of the characteristics of various herbaceous plants. In this study, we used 318 common herbaceous plants in Shaanxi as experimental material to investigate leaf area (LA), leaf fresh weight (LFW) and leaf dry weight (LFW) of them. Their CSR strategies were determined using the 'StrateFy' analysis tool and were presented in a triangular distribution. The results showed that S-selection was responsible for the vast majority of herbaceous plants in garden design, C- selection took second place, and R- selection was the least. Sub-strategy (CS, S/CS, CR, CS/CSR, S/CSR and so on) also played a vital role in garden plants, which together accounted for 90.88% from all plant strategies. In terms of the representative families, the strategies of Labiatae and Asteraceae distributed widely, and the trade-off appeared in C-S axes of Gramineae and Liliaceae. Among three leaf traits, LA was of great importance to C- strategy, LDMC to S- strategy, and SLA was important to R-strategy. CSR strategy composition indicates the power of artificial selection, and reasonable collocation of different CSR strategies can create a better community. Thus, we propose that future investigations on CSR strategies in different regions all over the world should provide a reliable database for garden herbaceous species selection.